Deposit insurance, moral hazard and bank risk - Karas, Alexei,Pyle, William,Schoors, Koen (CESifo, Center for Economic Studies & Ifo Institute, 2021)
Using evidence from Russia, we explore the effect of the introduction of deposit insurance on bank risk. Drawing on variation in the ratio of firm deposits to total household and firm deposits before the announcement of deposit insurance, so as to capture the magnitude of the decrease in market discipline after the introduction of deposit insurance, we demonstrate that larger declines in market discipline generate larger increases in traditional measures of risk. These results hold in a difference-in-difference setting in which private domestic banks serve as the treatment group and state and foreign-owned banks, whose deposit insurance regime does not change, serve as a control group.
10419/232464
Keywords: Graue Literatur; deposit insurance; market discipline; moral hazard; risk taking; banks; Russia